2015
DOI: 10.1007/s00464-015-4297-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open peritoneal dialysis catheter placement

Abstract: Using univariate analysis, there appears to be a benefit from LPDC placement. However, after controlling for confounding variables, the techniques appear to have equal outcomes. Surgeons should perform a LPDC or OPDC according to the approach with which they are most familiar. However, continued adoption, dispersal, and refinement of the laparoscopic approach may further optimize patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…The mean operating time was 41 minutes (range: 35-56 minutes). Although laparoscopic surgery often lasts more than laparotomy [15] in our laparoscopic technique, both operations lasted about 15-17 minutes that can be described as a superiority to other laparoscopic or laparotomy revision modalities and provided the permanent catheter function by using of the catheter fixation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean operating time was 41 minutes (range: 35-56 minutes). Although laparoscopic surgery often lasts more than laparotomy [15] in our laparoscopic technique, both operations lasted about 15-17 minutes that can be described as a superiority to other laparoscopic or laparotomy revision modalities and provided the permanent catheter function by using of the catheter fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Type of the technique of catheter insertion (laparoscopy versus open surgery) affects the incidence of catheter-related complications and survival of catheter; laparoscopic insertion technique provides a higher survival and less migration [1]. Current clinical practice guidelines indicated that there is not any proof to confirm the association between the type of catheter and the rate of its malfunctioning [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both open and laparoscopic techniques have been utilized to insert the Tenckhoff catheter to use for PD . Since the commencement of laparoscopic insertion, conflicting literature exists as to the safest procedure that minimizes risks of catheter malfunction (obstruction/migration), peritonitis, bleeding, pain and improving recovery time . Qiao et al .…”
Section: Introductionmentioning
confidence: 99%
“…2 Since the commencement of laparoscopic insertion, conflicting literature exists as to the safest procedure that minimizes risks of catheter malfunction (obstruction/migration), peritonitis, bleeding, pain and improving recovery time. 1,[3][4][5] Qiao et al 4 performed a systematic review in 2016 when comparing open technique versus laparoscopic technique. This found the laparoscopic technique to be superior in reducing catheter migration and prolonging catheter survival.…”
Section: Introductionmentioning
confidence: 99%